Film, photo, and text: relation-making, intensive genres, and realism - Schaflechner, Jürgen; Kramer, Max (Dastavezi, 2021)
Throughout Dastavezi’s brief existence, this introduction has become a train of thought and a conversation for both of us, where we reflect on the ever-changing landscape of multi-mediated forms of knowledge production in and from South Asia. This reflection—which we called Slow Theory—emerges from two of our fundamental convictions: 1.) New ways of theorizing the world demand thinking with and through new forms of art and media. 2.) Phenomena from the Global South help to “air out” (Viveiros de Castro 2003) a form of theory that has become accustomed to utilizing mainly North American and European case studies and philosophers. In this issue, we, therefore, increase Dastavezi’s range of used media to include photo essays reflecting on the potentialities of image and text regarding labor migration in Kerala (Karinkurayil) and religious nationalism in Pune (Larios).